Perancangan sistem komunikasi client server PLC (Power line Communication ) pada instalasi jaringan listrik studi kasus Jurusan Elektro Politeknik Negeri Pontianak - Muhammad Diponegoro; Rusman Rusman; Wendy Yuniarto; Ruskardi Ruskardi (Jurnal ELIT, 2023)
The existence of this internet needs to be supported by a stable wireless network signal The development of network infrastructure and the internet has now penetrated into various fields. Pontianak State Polytechnic (POLNEP) is one of the vocational higher education institutions in Pontianak that uses the internet as a learning medium, including the Department of Electrical Engineering. However, at this time the internet network in the Department of Electrical Engineering, Pontianak State Polytechnic, along with the increasing number of lecturers and students, became unstable and slow and could not reach all places and affected student activities carried out. One of the causes is the limitation on the access point signal or wireless internet transmitter hotspot. The purpose of this study is to implement Power Line Communication (PLC) in the Department of Electrical Engineering Polnep as an alternative network delivery media and perform measurement results on the value of delay, Packet Loss Ratio and Bandwidth